Association of Anticardiolipin Antibodies and Extent of Coronary Artery Disease in Military Personnel and Non Military Population With Acute Coronary Syndrome - Bahareh Hajibaratali; Shahram Baharvand; Shahrooz Yazdani (International Journal of Cardiovascular Practice, 2016)
Introduction: Cardiac involvement is one of the chief complications considerably contributing to the morbidity and mortality of patients with systemic autoimmune diseases. Anticardiolipin antibody is a marker of elevated myocardial infarction risk and it also predicts post cardiac intervention risk. In the current study, we aimed to evaluate the association between anticardiolipin IgM and IgG levels and atherosclerotic involvement of coronary arteries.Methods: Patients with acute coronary syndrome admitted to a military hospital were included in the study. Patients were categorized to military personnel and non-military personnel. Laboratory data including lipid profile, blood sugar, anticardiolipin IgM and anticardiolipin IgG were verified. Existence and the extent of Coronary Artery Disease (CAD) were defined according to angiographic findings. The relationship between anticardiolipin antibody levels and the number of vessels were evaluated.Results: According to our sample population calculation, we performed the study on a total of 92 patients. Measurement of both anticardiolipin antibodies (IgM and IgG) in military personnel and non personnel patients showed no significant difference. In both military personnel and non personnel groups, there was a significant association between anticardiolipin IgM and IgG levels and number of coronary arteries with significant stenosis. The C Reactive Protein (CRP) level was significantly higher in military personnel.Conclusions: According to the study results, anticardiolipin antibody levels were the same in both military personnel and non personnel. Also systolic and diastolic blood pressures were not significantly different in both groups. Increased CRP level in military personnel may be a warning signal about the possibility of premature CAD in this population, hence aggressive risk factor modification is recommended. Paradoxically lipid profile and FBS levels were more favorable in military personnel, which indirectly reflects their higher state of physical activity.